Monte Carlo dosimetry study of novel rotating MRI-compatible shielded tandems for intensity modulated cervix brachytherapy. (March 2020) - Morcos, Marc; Enger, Shirin A.
Highlights: Rotating shield IMBT enables dose modulation to better conform to tumor and reduce OAR doses. Three novel rotating tandem shields were designed and simulated using RapidBrachyMCTPS. Ir-192, Se-75 and Yb-169 were investigated as potential IMBT sources. Dynamic IMBT achieves substantial dose modulation even with the Ir-192. IMBT with sup-inf directional modulation enabled needle-free cervix brachytherapy. Abstract: Purpose: Intensity modulated brachytherapy (IMBT) with rotating metal shields enables dose modulation that can better conform to the tumor while reducing OAR doses. In this work, we investigate novel rotating shields, compatible with MRI-compatible tandems used for cervix brachytherapy. Three unique shields were evaluated using the traditional 192 Ir source. Additionally, 75 Se and 169 Yb isotopes were investigated as alternative sources. Methods: Three different IMBT shields were modeled and simulated in RapidBrachyMCTPS. Each tungsten shield was designed to fit inside a 6 mm-wide MRI-compatible tandem. The active core of the source was replaced with 192 Ir, 75 Se and 169 Yb. Transmission factors (TFs) were calculated and defined as the dose ratio at 1 cm on opposite sides of the shielded tandem on the transverse plane. Polar and azimuthal anisotropy plots were extracted from simulations. Dose homogeneities V 200 % V 100 % were calculated for all radionuclide-shield combinations. Results: TFs are favorable for IMBT and ranged between 12.9% and 32.2% for 192 Ir, 4.0%-16.1% for 75 Se and 1.2–6.4% for 169 Yb for all shield designs. Average beam-widths in the polar and azimuthal directions were reduced to the range of 42°–112° and 27°–107°, respectively, for all shield-radionuclide combinations. Dose homogeneities for all the radionuclide-shield combinations were within 12% of the non-IMBT tandem. Conclusions: This study has quantitatively assessed the influence of various rotating cervical cancer-specific IMBT tandem shields on dosimetry. The dynamic single-channel shields and narrow beam-widths in the polar and azimuthal direction give rise to highly anisotropic distributions. Intermediate-to-high energy radionuclides, 75 Se and 169 Yb substantially improve the modulation capacity of IMBT and pave the way for treating large and complex cervical cancer without interstitial needle implantation.